2021
DOI: 10.1109/access.2021.3085370
|View full text |Cite
|
Sign up to set email alerts
|

Service Placement for Latency Reduction in the Fog Using Application Profiles

Abstract: The Cloud-Fog-Internet of Things continuum combines different paradigms to provide connectivity and ubiquity for end-users, while also granting low latency and low jitter to cope with different challenges, including the requirements of latency-sensitive applications, such as virtual/augmented reality and online gaming. This constitutes a complex and dynamic environment with heterogeneous resources that need to be managed or orchestrated, in order to accomplish application requirements for low latency. Common o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The level of service latency is an important indicator of the performance of edge systems. Velasquez et al [19] initially framed the challenge of edge service deployment as a linear programming problem, focusing on the optimization of latency. Subsequently, they introduced a PageRank-based heuristic algorithm, which assigns grades based on service request volume, and deployment decisions are made based on these grades.…”
Section: Reducing Average Latencymentioning
confidence: 99%
“…The level of service latency is an important indicator of the performance of edge systems. Velasquez et al [19] initially framed the challenge of edge service deployment as a linear programming problem, focusing on the optimization of latency. Subsequently, they introduced a PageRank-based heuristic algorithm, which assigns grades based on service request volume, and deployment decisions are made based on these grades.…”
Section: Reducing Average Latencymentioning
confidence: 99%
“…[10-14] [22, 24]. In community-based approaches, nodes are clustered based on connection density and organized as communities [21,24,25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The betweenness centrality measure is used to create a set of wellconnected devices to improve service availability. Velasquez et al [21] create groups of nodes based on the possibility of sharing gateway load between the nodes. To do this, they rank the nodes to form communities that contain nodes with the highest transition probability.…”
Section: Community Based Application Service Deploymentmentioning
confidence: 99%
“…Khosroabadi and Fotouhi-Ghazvini 5 proposed "a clustering of fog devices and requirement-sensitive services first" (SCATTER) algorithm to allocate the fog-edge border computing resources to delay-sensitive applications but ignores the other tasks in demand, which could be a concern in many real-life applications. 39 introduced popularity ranked placement (PRP) based on graph partitions and optimization using genetic algorithms, and showed that PRP yielded improvements compared to the generic genetic algorithm or first fit (FF) algorithm but could still be improved. Morkevicius and Venčkauskas 40 presented two stages of multiobjective optimization that included multiple metrics that we use in this study to evaluate the proposed method: security performance, compute usage performance, and storage utilization.…”
Section: Related Workmentioning
confidence: 99%